The Impact of Fintech Peer to Peer Lending and E-Money Transaction on Economic Growth: The Moderating Role of Inflation - Meliza; Ayuningrum Anggrainy Putri (E3S Web of Conferences)
The rise of financial technology (fintech) and digital transactions has transformed economic landscapes, particularly through peer-to-peer (P2P) lending and e-money transactions, both of which significantly contribute to economic growth. This study aims to examine the impact of fintech P2P lending and e-money transactions on economic growth, while also analyzing inflation as a moderating variable, which serves as a novel contribution to this research. Using secondary data from Bank Indonesia, this study applies multiple regression analysis with a random-effect model to assess the relationships between these financial innovations and economic growth. The findings indicate that fintech P2P lending has a significant positive effect on economic growth, with a z-statistic value of 15.32, while e-money transactions also exhibit a significant positive impact, with a z-statistic value of 8.03. Furthermore, inflation moderates these relationships differently: it weakens the positive impact of P2P lending on economic growth (z-statistic: -1.78) but enhances the influence of e-money transactions on economic growth (z-statistic: 1.78). These findings offer valuable insights for policymakers and fintech stakeholders, highlighting the critical role of inflation in shaping the effectiveness of fintech-driven financial inclusion. Understanding these dynamics can help optimize fintech policies, enhance digital financial services, and sustain economic growth in an increasingly digitalized economy. Future research could explore additional macroeconomic variables and alternative financial indicators to further enrich the discussion on fintech’s role in economic development.